2020
DOI: 10.1785/0220200092
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Background Seismicity Rate and Evolution of Stress Changes in the Changning Salt Mining and Shale-Gas Hydraulic Fracturing Region, Sichuan Basin, China

Abstract: The Ms 6.0 earthquake in Changning, Sichuan, China, on 17 June 2019 was the largest recorded earthquake in the stable Sichuan basin. It occurred in a complicated region with salt mining and shale gas production. Whether this earthquake is induced raises concerns among the public and the scientific community. Furthermore, the relation between this earthquake and nearby industrial activities has also been of great interest. To address these questions, we estimated the nonstationary background seismicity rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…On the other hand, the region also contains active fluid injection for solution mining of salt (Figure 1b), which is spatially much closer to the sequence and has induced earthquakes during past operations (e.g., Sun et al, 2017). Accordingly, the sequence could be potentially associated with salt mining, which was also suggested by three recent seismological studies (Jia et al, 2020;Lei et al, 2019b;Liu & Zahradník, 2020). Moreover, Lei et al (2019b) regarded that the 2018 Ms 5.7 earthquake in the shale gas block (Figure 1b) could also bring the Changning sequence closer to failure.…”
Section: Introductionmentioning
confidence: 68%
“…On the other hand, the region also contains active fluid injection for solution mining of salt (Figure 1b), which is spatially much closer to the sequence and has induced earthquakes during past operations (e.g., Sun et al, 2017). Accordingly, the sequence could be potentially associated with salt mining, which was also suggested by three recent seismological studies (Jia et al, 2020;Lei et al, 2019b;Liu & Zahradník, 2020). Moreover, Lei et al (2019b) regarded that the 2018 Ms 5.7 earthquake in the shale gas block (Figure 1b) could also bring the Changning sequence closer to failure.…”
Section: Introductionmentioning
confidence: 68%
“…Peña-Castro et al, 2020) and the Sichuan Basin (e.g. Jia et al, 2020). We note that these two plays represent the two most extreme cases of HF-IS, with the Sichuan Basin hosting the largest HF-IS events yet recorded, with the Montney shale being the secondlargest, and also showing the most extreme examples of magnitude jumps during injection.…”
Section: Influence Of Stress Conditions On the Evolution Of Hf-is Seqmentioning
confidence: 76%
“…Lei et al (2019) reported further HF-IS in the same region, focussing on pad N201, which produced an M 5.7 earthquake in December 2018. We note that caution may be required with these events, since recent studies have linked some of the induced seismicity that has occurred in the Sichuan Basin with salt mining processes rather than hydraulic fracturing (Lei et al, 2019b;Jia et al, 2020).…”
Section: Sichuan Basin Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling non-stationary seismicity brings complications far beyond those of steady state. With sufficient data these have already been addressed successfully by ETAS models [14][15][16]18,20,21 . But since our purpose is to consider the added complication of small catalogs we therefore choose as an alternative the Gamma form (1).…”
Section: Resultsmentioning
confidence: 99%